2022
DOI: 10.1002/jmri.28352
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Diffusion‐Tensor Imaging Evidence for Trans‐Synaptic Axonal Degeneration in Dysthyroid Optic Neuropathy Due to Thyroid‐Associated Ophthalmopathy

Abstract: BackgroundThe mechanism driving dysthyroid optic neuropathy (DON) is unclear. Diffusion‐tensor imaging (DTI) allows for noninvasively assessing the microstructure of the entire visual pathway and may facilitate a better understanding of the mechanism of DON.PurposeTo assess microstructural changes of the whole visual pathway and to investigate the potential mechanism of trans‐synaptic damage(TSD) pathogenesis in DON with DTI.Study TypeCross‐sectional.PopulationSixty‐four patients with bilateral thyroid‐associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The correlation results further demonstrated the possibility of utilizing DTI to assess visual pathway changes in TAO, showing that disruptions in the visual pathway progress along with increased inflammation and crowding of the orbital tissues. As previous research stated ( 12 ), OR–MD showed no significant correlation with any of the clinical variables, which were consistent with our study. While the OR–FA was positively correlated with VA and IOP, which is in direct contrast to our findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The correlation results further demonstrated the possibility of utilizing DTI to assess visual pathway changes in TAO, showing that disruptions in the visual pathway progress along with increased inflammation and crowding of the orbital tissues. As previous research stated ( 12 ), OR–MD showed no significant correlation with any of the clinical variables, which were consistent with our study. While the OR–FA was positively correlated with VA and IOP, which is in direct contrast to our findings.…”
Section: Discussionsupporting
confidence: 93%
“…However, current research on the TAO visual pathway is mainly limited to the intraorbital optic nerve, and there is very little research on other parts of the optic pathway. Liu et al ( 12 ) evaluated the microstructural changes along the whole visual pathway in TAO patients using DTI. The result of our findings is consistent with the findings of Liu et al: the visual pathway FA and MD values are associated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversy still exists regarding the pathogenesis of DON as it appears to be multifactorial 4 . Recent neuroimaging studies reported alterations of the brain structure and function in regions associated with vision in DON patients 5,6 . Therefore, current evidence suggests that patients with DON may demonstrate neural alterations in the visual pathway of DON.…”
mentioning
confidence: 99%
“…4 Recent neuroimaging studies reported alterations of the brain structure and function in regions associated with vision in DON patients. 5,6 Therefore, current evidence suggests that patients with DON may demonstrate neural alterations in the visual pathway of DON. However, the exact structural and functional brain network alterations in DON remain elusive.In this issue of JMRI, Zhang et al further examined the morphological and functional brain alterations in DON using resting-state functional MRI (rs-fMRI).…”
mentioning
confidence: 99%